New laboratory biomarkers of rheumatoid arthritis - D. A. Dibrov (Научно-практическая ревматология)
The review presents data on new biomarkers for the diagnosis of rheumatoid arthritis, considers the diagnostic parameters of antibodies to carbamylated proteins, antibodies to peptidyl arginine deaminase, antibodies to homocysteinylated α1-antitrypsin, 14-3-3η, macrophage soluble scavenger receptor A. The use of new biomarkers can improve the diagnosis of RA in the early stages, as well as stratify patients based on the prognosis of the disease and provide a rational selection of therapy.